Transcriptome Sequencing of the Pale Anemones (Exaiptasia diaphana) Revealed Functional Peptide Gene Resources of Sea Anemone - Fu, Jinxing; He, Yanbin; Peng, Chao; Tang, Tianle; Jin, Aihua; Liao, Yanling; Shi, Qiong; Gao, Bingmiao (Frontiers in Marine Science, 2022)
Sea anemone venom contains a complex and diverse arsenal of peptides and proteins of pharmacological and biotechnological interest, however, only venom from a few species has been explored from a global perspective to date. The primary objective of this study was to realize large-scale discovery of protein and peptide toxin sequences from different developmental stages of the sea anemone Exaiptasia diaphana. Using high-throughput transcriptome sequencing, we identified 533 putative protein and peptide toxin sequences that belong to 75 known superfamilies, in which most of the protein components corresponded to metalloproteases, pancreatic lipase-related protein like, chymotrypsinogen like, collagen, and G-protein coupled receptor, and the peptide components corresponded to ShK domain, Kunitz-type, thrombin, defensin, and insulin-like peptide. This study therefore provides a valuable high-throughput method to obtain the resources of sea anemone proteins and peptides, and lays a foundation for further targeted research on the diversity and pharmacological effects of sea anemone toxins.